Performance and Exhaust Emissions of Four Stroke Gasoline Engine Variations of Injection Duration Mapping with Ethanol Fuel E75 - Muhamad Khoirul Anam; Mohammad Lutfiyanto; Adi Mulyadi; Wisnu Kuncoro (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2025)
Ethanol is a biofuel in which its storage and physical condition are almost the same as gasoline (fuel oil). It is still possible to drive a gasoline engine with ethanol in low concentrations. However, applying high concentrations to gasoline engines will require modifications, such as changing injection duration and compression ratio. This is done to get better performance and emissions than the use of gasoline fuel. In this study, the gasoline engine used was a 177cc single-cylinder four-stroke engine with E75 (75% Ethanol and 25% Pertalite), where the test engine was modified on the injection duration section with the replacement of standard ECU components into a programmable ECU. The replacement aims to facilitate changes in engine parameters, such as injection duration. In injection duration mapping, basic mapping values are added by 2%, 4%, 6%, and 8%. Then, the compression ratio is changed from 11:1 to 13:1. In comparison, testing is performed under standard machine conditions using Pertalite (E0). To test engine performance, a Prony brake dynamometer is used, while to test exhaust emissions are used exhaust gas analyser. E75 fuel use in the study resulted in torque and power increased by 30% and 19% with additional injection duration (8%) and (6%). However, in E75 use the duration of injection (2%) and (4%) decreased. This is related to AFR values, where injection duration (2%) and (4%) run on lean AFR. Then the SFC result increases, which is affected by the low heat value of ethanol fuel. And the use of ethanol E75 can reduce CO and HC emissions by 69.5% and 17% respectively.